As relações entre as personagens de Memórias Póstumas de Brás Cubas e Quincas Borba - Moreira, Ana Paula Moutinho (2009)
This dissertation treats of the relations between the characters of Machado de Assis novels Memórias Póstumas de Brás Cubas (1881) and Quincas Borba (1891), and relations like power. Among the ways of power analysed in this research are the power of money, seduction and culture. So, it is highlighted in what manner the ways of power are established between the characters of the two novels. As main historical source is Raymundo Faoro s work Os donos do poder, because apart from historical subsides, it can also be found elements that allow us to make a relation between those owners of power and their similars in the two novels by Machado de Assis. As the study object of this work is a work of art, which is, an esthetic product, it is also valued the author s work as a creator, who uses specific tools of literature creation. This work is structured in four manners. At first it treats of the relations between literature and society; later it will treat of the relation of power that exists in the character of the narrator of Memórias Póstumas de Brás Cubas; further on it will treat of the ways of power which are present in the two chosen works by Machado de Assis as study object and finally it will treat of the relations of power between the characters of Memórias Póstumas de Brás Cubas and Quincas Borba.